Architecture and Aging: The Depiction of Home in Sarah Polley’s Away From Her - Adams, Annmarie; Chivers, Sally (Age, Culture, Humanities: An Interdisciplinary Journal, 2015)
Our paper focuses on Sarah Polley’s flm Away from Her as a commentary on places purposely constructed for care. We draw on cultural and architectural analysis to uncover the flm’s reassertion and yet subtle critique of the troubling association of aging with decline, to which dementia provides a shortcut. We analyze the flm’s architectural nod to themes of “home,” the importance of natural light, and the depiction of circulation spaces as a means to further understand the association of old age with darkness and disorientation. The paper shows how the flm’s projection of typologies of “home” is indicative of the continuities and ruptures experienced by residents with dementia and their family members. We demonstrate how Polley’s flm uses real-life architecture as a set, such that her characters (who are not yet elderly but who are experiencing what the general public understands to be disorders of old age) navigate the apparently dark and confusing interiors of long-term care, bathed in profuse natural light. While the flm is a drama about illness and love, the conficts about where to live, how to care, and what comprises fdelity, the role of long-term care architecture in Away from Her shows how twenty-frst-century lived experiences of dementia play out away from “home".